Examining the professional career values and career awareness of athlete- students: the sample of the faculty of sports sciences - Enver Döşyılmaz; Tayfun Şirin (Physical Education of Students, 2021)
Background and Study Aim. Athlete-students continue their athletic careers at a professional level during their education, or many try to pursue alternative career paths. While much attention has been given to Athlete-students' academic progress and graduation rates in the literature, little attention has been paid to their attitudes towards career values and career awareness. Therefore, this study aimed to determine the career awareness and career values of athletes-students according to some demographic variables.